Hydrogen-Induced Deformations of Metals Followed by in Situ Scanning Tunneling Microscopy : Palladium Electrolytic Hydrogen Charging and Discharging in Alkaline Solution - Andreasen, Gustavo (1999)
In situ scanning tunneling microscopy measurements of Pd single-crystal domains during hydrogen charging/discharging cycles in 0.25 M KOH at 298 K allowed us to follow deformations produced by the Pd ↔ S β(H-Pd) phase transition in real time. The stress produced by this transition leads to elastic deformations involving reversible volume changes and plastic deformations resulting in one- or two-atom high slip lines and slip bands. These results demonstrate the capability of nanoscopies to investigate solid deformations on the nanometer scale in different environments, discriminate different types of deformations, and distinguish possible additional steps that are involved in the dynamics of solids.